The faces of yesterday in a present story: Analysis from the realities of the war disabled in the municipality of Chinandega, 2019 (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This article is elaborated from the authors relationship with strategic actors belonging to to the war disabled guild in the municipality of Chinandega. The title The faces of yesterday in a present story- Analysis from the realities of the war disabled in the municipality of Chinandega, 2019. It aims to rescue some elements extracted from the orality emitted by these actors, same where historiographic aspects and reflections of the experiences of this group are related about their protagonism in the insurrection processes for national liberation. The purpose of this investigative article is to carry out a comprehensive and chronological analysis of the experiences and perspectives of some war disabled today. In the same way, it is intended to investigate their appreciations related to the current context of the country and its role in the consolidation of peace. The subject has been approached from the holistic-anthropological approach, using own methods and techniques such as ethnography, direct and participant observation, application of in-depth interviews key actors of the study.
Keywords: disabled; war; ages; guild; society; context